Authentic and People-Oriented Leadership Effects on Performance - Joni Ojak Faransius Sihaloho; Sandi Nasrudin Wibowo (IJEBD (International Journal of Entrepreneurship and Business Development), 2026)
Purpose: This study aims to examine the effects of Authentic Leadership and Employee-Oriented Leadership on employee performance, with work motivation as a mediating variable, at PT Astra Credit Companies Cirebon. Design/methodology/approach: This study uses a quantitative associative approach based on Partial Least Squares Structural Equation Modeling (PLS-SEM). The research sample consisted of 115 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed in SmartPLS. Findings: The results show that People-Oriented Leadership has a positive and significant effect on employee performance. Authentic Leadership has a positive and significant effect on employee motivation and employee performance. Employee motivation also has a significant effect on employee performance. Furthermore, employee motivation significantly mediates the relationship between Authentic Leadership and employee performance, but does not mediate the relationship between People-Oriented Leadership and employee performance. Research limitations/implications: This study is limited to a single financing company and has a relatively small number of respondents, which may limit the generalizability of the findings. Future research is recommended to include broader samples and different industry sectors. Practical implications: The findings suggest that financing companies should develop leadership styles that emphasize authenticity and employee orientation to enhance employee motivation and improve employee performance. Originality/value: This study provides empirical evidence on the role of Authentic Leadership and People-Oriented Leadership in influencing employee performance by incorporating work motivation as a mediating variable in the financing industry. Paper type: Research paper